Pectoralis Minor Syndrome: Case Presentation and Review of the Literature - Mohammed Abdallah; Mohammad Rachad Wehbe; Elias Elias; Muhammad Aghiad Kutoubi; Roger Sfeir (Case Reports in Surgery)
We present a case of a healthy young female with axillary vein compression caused by the pectoralis minor muscle. Diagnosis was made by clinical findings and dynamic venography. After pectoralis minor tenotomy, the patient had total resolution of her symptoms. Compression of the axillary vein by the pectoralis minor is a rare entity that needs a careful exam and imaging to reach its diagnosis and establish the appropriate treatment.